The emergence of Clostridium difficile ribotypes 027 and 176 with a predominance of the Clostridium difficile ribotype 001 recognized in Slovakia following the European standardized Clostridium difficile infection surveillance of 2016. (January 2020) - Novakova, Elena; Stefkovicova, Maria; Kopilec, Maria Garabasova; Novak, Martin; Kotlebova, Nina; Kuijper, Ed; Krutova, Marcela
Highlights: Between October and December 2016, 36 Slovak hospitals performed Clostridium difficile infection (CDI) surveillance. The overall mean CDI incidence was 2.8 (95% confidence interval 1.9–3.9) cases per 10 000 patient-days. The most prevalent ribotypes were 001 ( n  = 46, 59.0%) and 176 ( n  = 23, 29.5%). Almost all isolates showed reduced susceptibility to moxifloxacin ( n  = 73, 93.6%). A reduced susceptibility to metronidazole was observed in 13 primary fresh isolates. Abstract: Aim: To obtain standardized epidemiological data for Clostridium difficile infection (CDI) in Slovakia. Methods: Between October and December 2016, 36 hospitals in Slovakia used the European Centre for Disease Prevention and Control (ECDC) Clostridium difficile infection (CDI) surveillance protocol. Results: The overall mean CDI incidence density was 2.8 (95% confidence interval 1.9–3.9) cases per 10 000 patient-days. Of 332 CDI cases, 273 (84.9%) were healthcare-associated, 45 (15.1%) were community-associated, and 14 (4.2%) were cases of recurrent CDI. A complicated course of CDI was reported in 14.8% of cases ( n  = 51). CDI outcome data were available for 95.5% of cases ( n  = 317). Of the 35 patients (11.1%) who died, 34 did so within 30 days after their CDI diagnosis. Of the 78 isolates obtained from 12 hospitals, 46 belonged to PCR ribotype 001 (59.0%; 11 hospitals) and 23 belonged to ribotype 176 (29.5%; six hospitals). A total of 73 isolates (93.6%) showed reduced susceptibility to moxifloxacin (ribotypes 001 and 176; p  <  0.01). A reduced susceptibility to metronidazole was observed in 13 isolates that subsequently proved to be metronidazole-susceptible when, after thawing, they were retested using the agar dilution method. No reduced susceptibility to vancomycin was found. Conclusions: These results show the emergence of C. difficile ribotypes 027 and 176 with a predominance of ribotype 001 in Slovakia in 2016. Given that an almost homogeneous reduced susceptibility to moxifloxacin was detected in C. difficile isolates, this stresses the importance of reducing fluoroquinolone prescriptions in Slovak healthcare settings.